The hour I first believed : [large type] : a novel - Lamb, Wally (Harperluxe, 2008)
Relocating to a family farm in Connecticut after surviving the Columbine school shootings, Caelum and Maureen discover a cache of family memorabilia dating back five generations, which reveals to Caelum unexpected truths about painful past events.